Combined effects of warming and freshening on the physiological energetics of the edible whelk Trophon geversianus. (January 2020) - Détrée, Camille; Ortiz, Alejandro; Navarro, Jorge M.
Abstract: The interacting effects of climate change pressures and human use of natural resources are increasingly affecting marine biodiversity. Variations in key abiotic factors such as temperature and salinity may therefore negatively influence marine organisms that are already threatened by intensive fisheries. Herein, we tested the hypothesis that future ocean warming and freshening will affect the fitness and survival of the overexploited snail Trophon geversianus in Southern Patagonia. To test this hypothesis, we investigated the effect of a 50 day incubation period of five temperatures (1, 5, 9, 12 and 15 °C) and two salinities (25 and 30 psu), (which correspond to current and projected conditions for Antarctic and Sub-Antarctic regions), on the physiological energetics (ingestion rate, absorption efficiency, oxygen uptake and scope for growth (SFG)) of the edible whelk T. geversianus. Our results showed no significant effects for salinity or the combination of temperature and salinity on T. geversianus bioenergetics. On the contrary, incubation at low temperatures (1 and 5 °C) was shown to affect the ingestion rate, absorption efficiency, oxygen uptake and SFG for T. geversianus, whereas for specimens incubated at 12 and 15 °C, physiological rates remained similar to control. Our data suggests that T. geversianus might be robust to warming and future variations of salinity, but longer term experiments are needed to ensure that no reduction of performance will occur after an extended incubation time from an increase in temperature. Highlights: Warming and freshening do not affect the scope for growth of the snail T. geversianus . The scope for growth of T. geversianus is affected by lower temperatures (1 and 5 °C). The Trophon fishing stocks would resist the combined warming and freshening effect.